2015
DOI: 10.1007/s00425-015-2382-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses of Oryza sativa secondary metabolism to biotic interactions with cooperative, commensal and phytopathogenic bacteria

Abstract: Profiling of plant secondary metabolite allows to differentiate the different types of ecological interactions established between rice and bacteria. Rice responds to ecologically distinct bacteria by altering its content of flavonoids and hydroxycinnamic acid derivatives. Plants' growth and physiology are strongly influenced by the biotic interactions that plants establish with soil bacterial populations. Plants are able to sense and to respond accordingly to ecologically distinct bacteria, by inducing defens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…In addition, this metabolic reprogramming was characterized by amino acids, organic acids, HCA derivatives, hydroxybenzoic acids, fatty acids, and glycoalkaloids (Table 1). In previous studies, inoculation of rice and maize with Azospirillum species was reported to affect HCAs and benzoxazines, respectively, and strain-specific metabolic changes were observed [48,49]. Also, using different microbial-derived priming agents, [37] showed that lipopolysaccharides, chitosan, and flagellin petide (flg22) triggered the biosynthesis of HCAs, and these were specific to each priming agent.…”
Section: Metabolic Profiling Of Pgpr-inoculated Tomato Plantsmentioning
confidence: 93%
“…In addition, this metabolic reprogramming was characterized by amino acids, organic acids, HCA derivatives, hydroxybenzoic acids, fatty acids, and glycoalkaloids (Table 1). In previous studies, inoculation of rice and maize with Azospirillum species was reported to affect HCAs and benzoxazines, respectively, and strain-specific metabolic changes were observed [48,49]. Also, using different microbial-derived priming agents, [37] showed that lipopolysaccharides, chitosan, and flagellin petide (flg22) triggered the biosynthesis of HCAs, and these were specific to each priming agent.…”
Section: Metabolic Profiling Of Pgpr-inoculated Tomato Plantsmentioning
confidence: 93%
“…Secondary metabolite synthesis is a strategy used by plants to adapt to different environments and cope with stresses (Chamam et al 2015). Many plant secondary metabolites, such as terpenoids, phenols, and alkaloids, also have value as medicines, spices, pesticides, and additives (Murthy et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the four HCAA, N ‐ p ‐coumaroylputrescine (C29), N ‐feruloylputrescine (C37), N ‐feruloylcadaverine (C43), N ‐feruloylglycine (C48), as well as several HCA‐hexosides appeared to be strongly down‐accumulated in response to the bacterial pathogen B. glumae . A contrasted accumulation of phenolic acids has previously been reported in inoculated rice, indicating that plant use common metabolites to interact with microorganisms but in different ways (Chamam et al ). The contrasted detection of HCA derivatives between the PGPR versus the pathogen treatment could be due to a differential availability and hence efficiency of metabolites extraction caused by modifications of plant cell wall.…”
Section: Discussionmentioning
confidence: 90%
“…The contrasted accumulation of secondary metabolites, already reported in rice but without identification of the specific compounds (Chamam et al ), indicates that plant use common metabolites to interact with microorganisms but in different ways. Plants perceived surrounding microorganisms, either beneficial or pathogenic, via structural and conserved elements composing the microbe, named MAMPs (Microbe‐Associated Molecular Patterns).…”
Section: Discussionmentioning
confidence: 93%